Design and synthesis of a high potential ruthenium (II) tetraazatetrapyridopentaphene complex capable of two-electron reduction - Diaz, Nancy Ruth G. (ProQuest LLC, 2010)
We report the synthesis of a complex, [(phen)2Ru(tatpph)Ru(phen)2]4 (Ph4), which like its predecessor compound, [(phen)2Ru(tatppc)Ru(phen)2]4 (Pc 4+), can undergo two sequential 1-electron photoreductions in MeCN in the presence of a sacrificial reductant. The initial complex, Ph 4+, can be completely regenerated from the singly and doubly reduced forms by exposure to air, although the rate of regeneration for the second photoreduction is much slower than the first. Electrochemical studies have shown that this complex is not only capable of storing multiple reducing equivalents but these equivalents have stored potentials that are significantly higher than the complex Pc 4+ and are sufficient to reduce H+ to H2. The first and second reduction potentials for Ph4+ were determined to be at -0.53 and -0.96 V respectively, while the corresponding reduction potentials for Pc 4+ were found to be at -0.02 and -0.51 V, all reported vs. NHE. These results correlate very well with the MO calculations which predicted a Ph 4+ LUMO that is 0.56 eV higher in energy than the Pc 4+ LUMO. The internal coordination site, born out of the bridging ligand's bent structure, is also accessible to further structural modifications that may lead to improve photocatalytic properties for the complex.--Abstract.